2022
DOI: 10.1002/cjoc.202200194
|View full text |Cite
|
Sign up to set email alerts
|

Three‐Dimensionalsp2Carbon‐LinkedCovalent Organic Frameworks as a Drug Carrier Combined with Fluorescence Imaging

Abstract: Three-dimensional (3D) covalent organic frameworks (COFs) are crystalline porous polymers with potential in numerous high-tech applications, but the linkages involved in their synthesis are still rather limited. Herein, we report novel 3D sp 2 carbon-linked COFs fabricated by the formation reaction of C=C bonds and their application in fluorescence imaging. These new COFs, namely JUC-580 and JUC-581, show high stability and excellent light-emitting properties in solid state and dispersed in various solvents. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 51 publications
0
17
0
Order By: Relevance
“…Till now, very limited examples of CC linked COFs have been reported. [ 94,95 ] As we have already discussed, as the chain needs to propagate in all three dimensions, the limited reversibility of CC bond formation mostly leads to amorphous frameworks. But, 3D COFs are more suitable for applications like charge transport.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Till now, very limited examples of CC linked COFs have been reported. [ 94,95 ] As we have already discussed, as the chain needs to propagate in all three dimensions, the limited reversibility of CC bond formation mostly leads to amorphous frameworks. But, 3D COFs are more suitable for applications like charge transport.…”
Section: Discussionmentioning
confidence: 99%
“…In 2022, Liao et al reported two interesting 3D sp 2 carbon linked COFs, namely JUC‐580 and JUC‐581, through Knoevenagel condensation of tetrakis(4‐formylphenyl)silane (TFS) as a tetrahedral building unit, and 2,2′‐(1,4‐phenylene)diacetonitrile (PDAN) or 2,2′‐(biphenyl‐4,4′‐diyl)diacetonitrile (BPDAN) as 2D linkers. [ 95 ] Both COFs possessed large channels, permanent porosity, and excellent thermal and chemical stability. They showed luminescence in solid state and even suspended in various solvents.…”
Section: Design Principles Of Cc Linked Organic Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…The irreversible of C = C bond enables the framework to exhibit impressive stability under harsh conditions, and offers extended π conjugation throughout the framework for efficient electron transport, showing great potential applications in photocatalysis 20 23 . So far, the only example of 3D sp 2 carbon-linked COFs involves substituted acrylonitrile [−CH = C(CN)−] based on the Knoevenagel condensation between arylacetonitriles and aromatic aldehydes 17 , 24 . Nevertheless, the strong electron-withdrawing substitution of nitriles attached to the olefin bond makes the bond reversible, compromising the stability and the crystallinity of COFs 25 .…”
Section: Introductionmentioning
confidence: 99%
“…Through dedicated structural designs, many other functions, including photothermal/dynamic, sonodynamic, photoluminescence, can also be introduced into the COF nanocarrier to design the ondemand smart drug delivery systems. [23][24][25] Over the years, COF materials have been explored for potential drug delivery applications. E.g.…”
Section: Introductionmentioning
confidence: 99%